CGIAR Science Group Evaluations: Brief on Partnerships - Independent Advisory and Evaluation Service (2025)
Aligned to the CGIAR 2030 Research and Innovation Strategy, CGIAR has been expanding its global network of partners and changing the way it works with them to drive the transformation of food, land, and water systems. Guided by the 2022 CGIAR Engagement Framework for Partnerships and Advocacy, the portfolios of CGIAR’s Science Groups-Resilient Agrifood Systems (RAFS), Genetic Innovation (GI), and Systems Transformation (ST)-aimed to implement a more structured approach to partnerships, focusing on co-developing research, enhancing capacity sharing for development, and strengthening collaboration with the private sector.